The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1969
DOI: 10.1002/aic.690150412
|View full text |Cite
|
Sign up to set email alerts
|

The effect of surfactants on the flow characteristics of falling liquid films

Abstract: Experimental values of the wave length and wave velocity have been obtained far dilute sohtions of valeric and hexanoic acid for a vertical fulling liquid film. The wave length was unaffected by the surfactants for Reynolds numbers in the range 5 to 100; however, the wave velocity was decreased for increased surface concentrations of the two acids. This is in direct contradiction to previous theoretical work, and the explanation for the anomaly is that the free surface velocity is greatly retarded by the adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1971
1971
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Finally, figure 9(d) presents the wave velocity of the marginally unstable mode at neutral stability as a function of the wavenumber and for different amounts of surfactant. In agreement with previous experimental and theoretical studies (Strobel & Whitaker 1969;Cerro & Whitaker 1971), we find that the addition of surfactant decreases the wave velocity, and more so the higher the wavenumber. It is also notable that the variation with M tot is strictly monotonic, reaching an asymptotic limit for high surfactant concentrations.…”
Section: Effect Of the Total Amount Of Surfactantsupporting
confidence: 93%
See 1 more Smart Citation
“…Finally, figure 9(d) presents the wave velocity of the marginally unstable mode at neutral stability as a function of the wavenumber and for different amounts of surfactant. In agreement with previous experimental and theoretical studies (Strobel & Whitaker 1969;Cerro & Whitaker 1971), we find that the addition of surfactant decreases the wave velocity, and more so the higher the wavenumber. It is also notable that the variation with M tot is strictly monotonic, reaching an asymptotic limit for high surfactant concentrations.…”
Section: Effect Of the Total Amount Of Surfactantsupporting
confidence: 93%
“…The theoretical results by Whitaker (1964) also suggested that the wave velocity should increase with increasing elasticity of the interface. However, the experimental work of Strobel & Whitaker (1969) indicated that the free-surface velocity actually decreases for increased surfactant concentration and this was later confirmed experimentally and theoretically by Cerro & Whitaker (1971). The latter work also noted that surface velocity depends strongly on the surface elasticity and is only mildly affected by surfactant diffusivity and interfacial mass transport.…”
Section: Introductionmentioning
confidence: 79%
“…Since then, the flow in falling liquid films has been studied extensively through experimental measurements [10,45], low-dimensional modelling [46,47], and full numerical simulations [48]. The effects of many factors that influence the flow in falling films have been investigated, such as the effects of thermocapillarity [49], electric fields [50,51], and surfactants [52,53]. Different processes that may be involved in falling films have also been studied, such as heat transfer [54], mass transfer [55], chemical reactions [56], and phase change [57].…”
Section: Introductionmentioning
confidence: 99%
“…This result for the critical Reynolds number associated with insoluble surfactants has also been presented by Benjamin (1964) and by Anshus and Acrivos (1967). It was used originally by Strobel and Whitaker (1969) to estimate surface elasticities from wave inception line data, and more recently by Cerro and Whitaker (1971).…”
mentioning
confidence: 99%